Friction Characteristics of Synchronization Process Based on Tribo-Thermodynamics. (7th August 2018) - Yan, Hao; Xu, Zhaoping; Yuan, Juntang; Liu, Liang; Tan, Cao; Ge, Wenqing
Abstract : In order to improve the shift control accuracy and shift quality, the temperature and friction coefficient changing regularities of a friction cone during the synchronization process were investigated. The thermal-structural coupling model was established through tribo-thermodynamic analysis. The relevant experiment was carried out as well. The results show that the error between the experimental and simulated results is within 3%. Besides, the maximum temperature of the synchronous ring friction surface increases 1.8°C for every additional 50 N of shift force, while increases 1.1°C for every additional 200     r / min shift speed difference. Moreover, the friction coefficient declines rapidly first and then tends to be stable slowly during the synchronization process. The result of friction coefficient changing regularity lays a good theoretical basis for establishing an effective friction coefficient compensation control strategy.